Anti-inflammatory mechanisms of IFN-γ studied in experimental autoimmune encephalomyelitis reveal neutrophils as a potential target in multiple sclerosis - Miller, Nichole M.; Wang, Jun; Tan, Yanping; Dittel, Bonnie N. (Frontiers in Neuroscience, 2015)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) mediated by T helper (h)1 and/or Th17 CD4 T cells that drive inflammatory lesion development along with demyelination and neuronal damage. Defects in immune regulatory mechanisms are thought to play a role in the pathogenesis of MS. While an early clinical trial indicated that IFN-γ administration was detrimental to MS, studies in the mouse model of MS, experimental autoimmune encephalomyelitis (EAE), indicated that IFN-γ exhibits a number of anti-inflammatory properties within the CNS. These mechanisms include inhibition of IL-17 production, induction of regulatory T cells, T cell apoptosis and regulation of chemokine production. Mice deficient in IFN-γ or its receptor were instrumental in deciphering the anti-inflammatory properties of IFN-γ in the CNS. In particular, they revealed that IFN-γ is a major regulator of neutrophil recruitment into the CNS, which by a variety of mechanisms including disruption of the blood-brain-barrier (BBB) and production of reactive oxygen species are thought to contribute to the onset and progression of EAE. Neutrophils were also shown to be instrumental in EAE relapses. To date neutrophils have not been appreciated as a driver of MS, but more recently based largely on the strong EAE data this view is being reevaluated by some investigators in the field.